INTELLECTUAL PROPERTY MANAGEMENT IN FOOTBALL CLUBS: STRATEGY AND TACTICS TECHNIQUES (On the example of FC "Rubin" municipal institution) - G. I. Gumerova; E. S. Shaimieva (Russian Journal of Economics and Law, 2014)
Objective: to form the conceptual framework in the field of intellectual property management in football clubs, to develop directions of intellectual property management development in FC "Rubin" (Kazan). Methods: general scientific methods of theoretical and empirical knowledge. Results: the notions "intellectual property management in football clubs" and "management of corporate image of the football club" are differentiated; the methodological approach to the management of the company's value is developed basing on tangible and intangible assets management; the issues of intellectual property objects patenting in the Russian sports (football) are studied; the management of Russian and foreign football clubs is analyszed; th system of intellectual property management in FC "Rubin" (Kazan) is diagnosed. Scientific novelty: the authors have developed the method of evaluation of intellectual property management in the football club based on the methodology for assessing the value of the brands of football clubs by Brand Finance consulting company (UK); generic and specific indicators are distinguished in the intellectual property management in a football club as in the intellectual property and corporate image management. Practical value: the recommendations are formulated in the format strategy and tactics techniques, concerning the industrial property management, confidential documented information, copyright for the intellectual property management in FC "Rubin" (Kazan).